THE ROLE OF STATE ADMINISTRATIVE COURTS IN ENSURE PROTECTION OF CITIZENS' RIGHTS - Agus Siagian (PT. Radja Intercontinental Publishing, 2025)
Study This aim For analyze role State Administrative Court (PTUN) in ensure protection right citizens towards​ decision administration government . Research This use approach law normative with method descriptive analytical , through studies literature from regulation legislation , PTUN decisions , and literature scientific latest (2020–2025). Research results show that the PTUN has function strategic as institution supervisor administration government that guarantees certainty law , justice , and accountability decision administration . PTUN handles various type dispute administration , starting from decision giving permits , sanctions administrative , up to policy public that impacts rights​ citizens . The effectiveness of the PTUN is influenced by several factors like certainty law , competence of judges, accessibility citizens , transparency institutions , mechanisms implementation decisions and support system administration government . Strategy for improving The role of the PTUN includes improvement literacy law community , transparency of court processes , training apparatus , as well as strengthening coordination with agency related . Research This confirm that the PTUN is not just a resolution forum dispute administrative , but also an instrument preventive measures that encourage good governance and protection right citizens in general effective .